Polymerase chain reaction assay targeting cytochrome b gene for the detection of dog meat adulteration in meatball formulation - Rahman, Md. Mahfujur; Ali, Md. Eaqub; Abd Hamid, Sharifah Bee; Mustafa, Shuhaimi; Hashim, Uda; Hanapi, Ummi Kalthum (Elsevier, 2014)
A polymerase chain reaction (PCR) assay for the assessment of dog meat adulteration in meatballs was developed. The assay selectively amplified a 100-bp region of canine mitochondrial cytochrome b gene from pure, raw, processed and mixed backgrounds. The specificity of the assay was tested against 11 animals and 3 plants species, commonly available for meatball formulation. The stability of the assay was proven under extensively autoclaving conditions that breakdown target DNA. A blind test from ready to eat chicken and beef meatballs showed that the assay can repeatedly detect 0.2% canine meat tissues under complex matrices using 0.04 ng of dog DNA extracted from differentially treated meatballs. The simplicity, stability and sensitivity of the assay suggested that it could be used in halal food industry for the authentication of canine derivatives in processed foods.